Low-Cost Customized Cranioplasty with Polymethyl Methacrylate Using 3D Printer Generated Mold: An Institutional Experience and Review of Literature - Chaudhary, Ankit; Sinha, Virendra Deo; Chopra, Sanjeev; Shekhawat, Jitendra; Jain, Gaurav (Indian Journal of Neurotrauma, 2021)
Background Cranioplasty is performed to repair skull defects and to restore normal skull anatomy. Optimal reconstruction remains a topic of debate. Autologous bone flap is the standard option but it may not be available due to traumatic bone fractures, bone infection, and resorption. In this article, the authors presented their experience with prefabrication of precise and low-cost polymethyl methacrylate (PMMA) mold using three-dimensional (3D) digital printing.Materials and Methods A total of 30 patients underwent cranioplasty between March 2017 and September 2019 at Sawai Man Singh Medical College Jaipur, India. Preoperative data included diagnosis for which decompressive craniectomy was done and Glasgow coma scale score. Intraoperative data included operating time. Postoperative data included cosmetic outcome in the form of cranial contour and margins, complications such as infection, seroma, implant failure, wound dehiscence, and hematoma.Results Patient age at cranioplasty ranged from 12 to 63 years with a mean age of 36.7 years. The mean operating time was 151.6 minutes (range 130–190 minutes). The mean follow-up period was 8 months (range 6–13 months). Postoperative wound dehiscence developed in one case (3.3%). Cranial contour and approximation of the margins were excellent and aesthetic appearance improved in all patients.Conclusion Low-cost PMMA implant made by digital 3D printer mold is associated with reconstruction of the deformed skull contour giving satisfactory results to the patient and his family members, at a low cost compared with other commercially available implants. This technique could be a breakthrough in cranioplasty.
Keywords: contour; cranioplasty; customized; mold; resin